Determinant Of Digital Bank Usage In Indonesia - Safira Larasati Owen; Zaenal Arifin (UNIVED Press, 2025)
This study aims to determine the factors influencing the use of digital banks in Indonesia. The research is developed from the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). This study employs a quantitative approach where data is obtained through a Google Form questionnaire. The research uses a sample of 179 digital bank users spread across Indonesia. The analysis used in this study is PLS-SEM. The results show that performance expectancy has a positive and significant impact on the behavioral intention, effort expectancy has a positive and significant impact on use, social media has a positive and significant impact on behavioral intention and use. trust have a positive and significant impact on behavioral intention and use, and the behavioral intention has a positive and significant impact on use. However, performance expectancy negatively impacts use,and effort expectancy negatively impacts behavioral intention